Desain Ulang Tata Letak Fasilitas Produksi Menggunakan Metode Systematic Layout Planning Pada Pabrik Kelapa Sawit Sungai Pagar - Choir, Mustofa; Arief, Dodi Sofyan; Siska, Merry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
PTPN V PKS-SPA is a state owned company that produces Crude Palm Oil (CPO) and Kernel. The problem that happened in this company is a material transfer distance is too far. Thus it is necessary to redesign the production floor to minimize material displacement distance. The design of the production floor layout will use the method of Systematic Layout Planning (SLP) and also with the help of software blocplan. SLP method is a method in the layout of the production facility that is able to overcome the problems of production flow by means of analyzing the flow of materials, make some diagrams, and then make alternative design and ends with the evaluation of the design. While blocplan software is a program that helps in planning the layout of the production facility in rectangular shapes by using input data including qualitative and quantitative data. With SLP method and also software blocplan obtained three alternative production floor layout. The first alternative is the transfer of a total distance of 78.5 m, 80.5 m alternative second and third alternative is 68.5 m, so that a third alternative selected for the smallest distance moved by the flow of materials. After alternate layout is determined, then the design of the production floor layout drawn in SketchUp software.Keywords: layout, SLP, blocplan, SketchUp